A description of spinal fatigue strength. Issue 6 (11th April 2016) - Huber, Gerd; Nagel, Katrin; Skrzypiec, Daniel M.; Klein, Anke; Püschel, Klaus; Morlock, Michael M.
Abstract: Understanding fatigue failure of the spine is important to establish dynamic loading limits for occupational health and safety. In this study experimental data were combined with published data to develop a description of the predictive parameters for spinal fatigue failure. 41 lumbar functional spinal units (FSUs) from cadaveric spines (age 49.0±11.9 yr) where cyclically loaded. Three different levels of sinusoidal axial compression (0–3 kN, 0–2 kN or 1–3 kN) were applied for 300, 000 cycles. Further, published data consisted of 70 thoracic and lumbar FSUs loaded in axial compression for 5000 cycles. Cyclic forces ranged from lower peaks ( F min ) of 0.7–1 kN to upper peaks ( F max ) of 1.2–7.1 kN. Based on Wöhler analysis, a fatigue model was developed accounting for three parameters: I) specimen-specific scaling based on the endplate area, II) specimen-specific strength dependency on age or bone mineral density, III) load-specific correction factors based on F max and F min . The most predictive model was achieved for a combination of F max, endplate area and bone mineral density; this model explained 61% of variation ( p <0.001). A model including F max, endplate area and age explained only 28% of variation ( p <0.001). Inclusion of a load-specific correction factor did not significantly improve model prediction of fatigue failure. This analysis presents the basis for the prediction of specimen-specific fatigue failure of the lumbar spine, provided the endplate area and bone mineral density can be derived.